Social Media and Consumerism Culture: A Study on Students of Universitas Dinamika Bangsa - Yossinomita, Yossinomita; Permatasari, Devita; Monica, Agnes; Diana, Diana; Chandra Dinata, Anglelika (CV. Satria Jaya, 2025)
This study is motivated by the increasing use of social media among students at Universitas Dinamika Bangsa, which is suspected to influence their consumerist lifestyle. The purpose of this research is to examine the impact of social media on students’ purchasing habits. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 92 enrolled students. The independent variable in this study is the intensity of social media use, while the dependent variable is the level of student consumerism. Data were analyzed using simple linear regression. The findings indicate that the intensity of social media use has a significant effect on students’ consumerism levels. The higher the intensity of social media use, the greater the tendency for students to purchase non-essential goods. These results highlight the need for enhancing students’ digital literacy skills to enable them to respond more critically to social media content, particularly promotional materials. The novelty of this research lies in its focus on the relationship between social media and consumerism among university students—a segment of the young generation that is particularly susceptible to the influence of a consumerist lifestyle.